BANJAR VILLAGE TOURISM DEVELOPMENT STRATEGY IN SUPPORTING ONE VILLAGE ONE DESTINATION (OVOD) BANYUWANGI DISTRICT - Vitasari, Leni (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
OVOD Model (One Village One Destination) is an approach to developing village potential to produce tourism products that are able to compete in the international market, while still having the unique characteristics of the area. The resulting product is a product that utilizes local resources, both natural resources and human resources. The research questions are divided into three namely; (1) How to improve the quality of sustainable resource management in Bukit Taman Langit Village, Banjar Village, Banyuwangi Regency? (2) How to increase the availability of goods and services by maximizing the available resources in a sustainable manner?, and (3) How to improve people's quality of life?. A qualitative method with an ethnographic approach is used in this study. Ethnography refers to the specificity of writing and reporting based on intensive field research. Data were collected through literature study, observation and in-depth interviews with resource persons. The three basic principles of the OVOD movement are: First, market area, namely the development of a tourist village approach to improve, develop and market tourism products that can be a source of pride for the local community, especially those that can be marketed domestically and abroad. Second, independence and creativity so that people are able to rise and be creative to produce products that have power selling. Third, the development of the quality of local human resources and their synergy with local governments, the private sector and other productive communities... The results of this study indicate that the implementation of the OVOD model is carried out by mapping the potential of natural and environmental resources, developing the potential and capabilities of human resources at the village level as dynamics of the village economy, as well as empowering local communities in managing the potential of their villages to increase added value. The main problem is the low progress of the village which is considered a tourist village. From several villages in Banyuwangi, there are still villages that are poor and have not been eradicated by poverty alleviation programs. Given the importance of productivity development in the context of economic development and growth, the problem of this research is formulated to what extent the OVOD model is able to become the basis for developing tourism economic productivity which is specifically described: (1) based on the characteristics of the OVOD model, with three main variables, namely physical, social and economics, (2) determine the success indicators of the OVOD model, and (3) formulate a strategy for using the OVOD model.